2010
DOI: 10.1021/ie1002608
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Ethanol from Carbon Dioxide Stripped Vapor Mixture: Adsorption Prediction and Modeling

Abstract: Carbon dioxide stripping of ethanol and adsorption can be used in a bioethanol fermentation system to reduce product inhibition. To gain a better understanding of the bioethanol adsorption process, a mathematical model was used to predict the adsorption performance of activated carbon WV-B 1500 for ethanol vapor adsorption in the presence of carbon dioxide and water. The model takes into account changes in velocity due to adsorption, heat effects during adsorption, and heat losses to the surroundings. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…The corresponding initial and boundary conditions for the energy balance in the column include: 18 13 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 at t = 0, T g = T 0 , for all z…”
Section: Energy Balance In the Columnmentioning
confidence: 99%
“…The corresponding initial and boundary conditions for the energy balance in the column include: 18 13 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 at t = 0, T g = T 0 , for all z…”
Section: Energy Balance In the Columnmentioning
confidence: 99%
“…Ponce et al [90] recovered 58% of the ethanol produced in the fermenter by gas stripping. Hashi et al [91] studied the recovery of ethanol from carbon dioxide stripped vapor mixture and validated their results with a mathematical model to predict the adsorption performance of activated carbon WV-B 1500 for ethanol vapor adsorption in the presence of carbon dioxide and water. Dominguez et al [92] showed an improvement in circulation, mass transfer and gas distribution in fermentationstripping process by using a special gas-lift loop reactor with external side-arm for xylose to ethanol conversion.…”
Section: Gas Strippingmentioning
confidence: 99%
“…Removing ethanol during the fermentation process is one possibility, since a high concentration of ethanol is toxic to yeast. There are some studies of pervaporation [39] and stripping [40] to take ethanol off the fermentation broth during the ethanol fermentation. The high cost of pervaporation membranes and the difficulty in recovering ethanol from CO 2 make this technology unfeasible nowadays.…”
Section: Fermentationmentioning
confidence: 99%